Growth effects of economic conditions at birth: the role of public funding for technology-based start-ups. Issue 6 (18th August 2022) - Huergo, Elena; López, Alberto
ABSTRACT: This article aims to evaluate the impact of public venture capital (VC) initiatives in the form of government-subsidized participative loans on the future growth of technology-based start-ups. We also analyze the role of the business cycle at the time of birth in firms' growth potential. To do this, we take advantage of a unique data set on Spanish technology-based start-ups that includes information about the profile of the technological entrepreneur at the time of birth and data on company accounts for the period 2001–2018. This information allows accounting for potential selection and endogeneity problems by using matching techniques. Our evidence is consistent with an effectiveness of this kind of public VC initiative to encourage firms' development through their medium-term effect on growth rates of sales and labor productivity and on intangible assets intensity, but only for start-ups created before the economic crisis. We also find that this latter set of start-ups has greater employment growth rates than other start-ups born during the crisis. These results are in line with the hypothesis that firms' growth is partly determined by the phase of the business cycle at the time of birth.